Pendampingan kader dalam pembuatan OVITRAP fermentasi perangkap nyamuk - Rustam Aji; Gustomo Yamistada; Sherly Ratih Frichesyarius Santi Aji; Roro Ajhie Ayuningtyas; Jessy Novita Sari (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
Mosquitoes have a radar that can detect various things. With this radar, mosquitoes detect an object by sensing the temperature emitted by the object. Government efforts have been made by distributing abate powder, fogging, mosquito nets and others. The purpose of community service activities is to reduce the mosquito population. The problem is that the mosquito population continues to grow. The method of solving the problem. Assistance of cadres in making fermented ovitraps for mosquito traps, benefits for cadres to increase knowledge and can teach the community in making fermented ovitraps as mosquito traps, so that they have opportunities to help others in their work. The conclusion of fermented ovitrap can help reduce the population of mosquito development, so that the surrounding community is free from dengue fever mosquito bites.